Analysis of self-reported discard information in Uruguayan industrial trawl fisheries - Luis Orlando; Daniel García (Ocean and Coastal Research)
Discarding unwanted catches is a significant issue arising from marine fishing activities, with far-reaching socioeconomic and ecological consequences. Uruguayan fishery regulations fail to penalize discarding but mandate self-reporting, providing an opportunity to analyze the discard from the two Uruguayan industrial bottom trawl fleets (shelf and coastal). By examining fishing logs, discard was estimated at 3,268 tons/year, accounting for 6.5% of the total catch (9.1% for the shelf fleet and 3.7% for the coastal fleet), with no discernible temporal trends for 2016, 2017, 2019, and 2020 nor significant seasonal variations in discard magnitude. Diversity, species richness, and evenness of the discard varied between fishing seasons and years. The most discarded species were Bassanago albescens in the shelf fleet and Brevoortia aurea in the coastal fleet. Both species showed magnitudes indicating a potential for exploitation development. Discard per unit of effort was mapped by fleet, enhancing the potential for discard information reconstruction for the area and thereby facilitating its inclusion in ecological and economic assessments. Discard reports have proven to be a valuable source of information that should be integrated into fisheries conservation and management initiatives.